The design of a mixed-reality book: Is it still a real book? - Grasset, Raphael; Dunser, Andreas; Billinghurst, Mark (2008 7th IEEE International Symposium on Mixed and Augmented Reality, 2008)
In this paper we present the results of our long term development of a mixed reality book. Most previous work in the area has focused on the technology of augmented reality books, such as providing registration using fiducial markers. In this work, however, we focused on exploring the design and development process of this type of application in a broader sense. We studied the semantics of a mixed reality book, the design space and the user experience with this type of interface.